Interferon alfa-2a modifies the course of subfoveal and juxtafoveal choroidal neovascularisation. Issue 10 (October 1994) - Engler, C; Sander, B; Villumsen, J; Lund-Andersen, H
Abstract : The first double masked placebo controlled trial of interferon alfa-2a for the treatment of overt choroidal neovascular membranes is presented. A total of 43 consecutive patients were randomised to double masked treatment with either interferon alfa-2a, 3 million IU subcutaneously three times a week or matching placebo, for a period of 8 weeks. End of study changes from baseline in distance and near visual acuity, macular visual field, contrast sensitivity, and macular morphology (fluorescein angiography) were assessed. The between group difference in distance visual acuity, the primary efficacy variable, was significant in favour of interferon alfa-2a (p = 0.023). Fluorescein angiograms, macular visual fields, and near vision all showed a trend in favour of interferon alfa-2a. It was concluded that, at the dosage used in this study, interferon alfa-2a is a reasonably well tolerated and apparently effective short term treatment of subfoveal and juxtafoveal choroidal neovascularisations.